AN ELEMENTARY AND NON-ELEMENTARY (EXTENDED) SENTENCE - Воробець, О. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of differentiation of elementary and non-elementary (extended) sentences of modern Ukrainian literary language that is with the question of interaction of the components of the extended sentence in the process of propositional basis formation of the sentence. It is emphasized that the sentences, which include the distributors, have the ability to function as representatives of a greater number of semantic roles (subject, object, attribute, locative, temporative, causative, etc.).